TWO USM FEMALE SCIENTISTS SECURED L'OREALUNESCO AWARDS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 20 Sept. 2016 – Two young female scientists from Universiti Sains Malaysia (USM) have put the name of the university in the limelight, at the same time achieving their personal best when they were selected to receive the L'Oréal-UNESCO Awards, which were created especially to acknowledge major contributions by female researchers in developing the scientific field in Malaysia.